Analisis Faktor-Faktor Permintaan Ekspor Timah Putih Indonesia oleh Singapura (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesia is endowed with abundant natural and human resources, which constitute vital capital for promoting national welfare, with the government serving as the primary steward in their utilization. This study seeks to investigate the influence of global tin prices, the exchange rate between the rupiah and the US dollar, domestic inflation rates, and national tin reserves on export demand. Employing time series data spanning from 1994 to 2023, the research adopts a multiple linear regression model to analyze the relationships among the variables. The findings indicate that, taken together, international tin prices (X1), exchange rates (X2), inflation (X3), and domestic tin reserves (X4) significantly affect the volume of Indonesia’s white tin exports to Singapore (Y). On an individual basis, global tin prices and the rupiah-to-dollar exchange rate exert a significant negative impact on export volume, while inflation and tin reserves exhibit a positive and statistically significant influence on tin export levels.